2009
DOI: 10.1086/595694
|View full text |Cite
|
Sign up to set email alerts
|

Complete Restriction of Fluoroquinolone Use to Control an Outbreak ofClostridium difficileInfection at a Community Hospital

Abstract: An outbreak of epidemic-strain HO-CDI was controlled at a community hospital after an overall decrease in antimicrobial use, primarily because of a restriction of FQ use and a change in environmental-services contractors. The restriction of FQ use may be useful as an adjunct control measure in a healthcare facilities during outbreaks of epidemic-strain HO-CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 31 publications
3
66
0
Order By: Relevance
“…Restricting the use of fluoroquinolones was associated with a significant reduction in the incidence of CDI, confirming fluoroquinolones as high-risk agents. 25,39 In addition, the analysis showed that the use of amoxicillin-clavulanic acid and macrolides was also positively correlated with the incidence of CDI. However, second-and third-generation cephalosporins did not appear as significant variables in the model, since their usage rate was already very low within the Trust.…”
Section: Resultsmentioning
confidence: 99%
“…Restricting the use of fluoroquinolones was associated with a significant reduction in the incidence of CDI, confirming fluoroquinolones as high-risk agents. 25,39 In addition, the analysis showed that the use of amoxicillin-clavulanic acid and macrolides was also positively correlated with the incidence of CDI. However, second-and third-generation cephalosporins did not appear as significant variables in the model, since their usage rate was already very low within the Trust.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to identify rapidly a cluster of patients in a hospital that is infected with the 027/NAP1/BI strain could be the key to implementing infection control efforts to halt transmission in the hospital, including restriction of fluoroquinolones (15,20,35). The 027/NAP1/BI isolates have the potential to produce high levels of spores and require enhanced environmental cleaning efforts for eradication (1,35).…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences between the sensitivities, specificities, or positive or negative predictive values of the results obtained with the Xpert C. difficile test and the results of PCR-ribotyping, REA, or PFGE (P Ͼ 0.05 for all comparisons) ( Table 4). The presumptive (17) 078 (14); 027 NAP7 (6); NAP1 CF (10) 017 (10) NAP9 (9) DH (19) 106 (14); 002, 046, 053 NAP11 (12) G (20) 002 (17); 104 Undefined types only J (22) 001 (7); 046, 056 NAP2 (7) K (8) 053 (6) Undefined types only Y (40) 020 (8) (11) 017 (11) CF (9); BK, Y NAP11 (24) 106 (13); 104 DH (12); G NAP12 (7) 087 (4) identification of the 027/NAP1/BI strain using the Xpert cartridge was available within 45 min of initiating the testing of the stool sample. Distribution of known C. difficile strains among study sites and analysis of congruence.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…In addition, fluoroquinolone exposure has been associated with colonization and infection with other healthcare-associated pathogens, including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Clostridium difficile [3-5]. Reducing the use of fluoroquinolones may be an effective strategy to limit the dissemination of these pathogens [6,7]. For example, a restriction program that resulted in a 66% reduction in use of fluoroquinolones was associated with control of an outbreak of C. difficile infection (CDI) associated with fluoroquinolone-resistant North American pulsed-field gel electrophoresis type 1 (NAP1) strains [7].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the use of fluoroquinolones may be an effective strategy to limit the dissemination of these pathogens [6,7]. For example, a restriction program that resulted in a 66% reduction in use of fluoroquinolones was associated with control of an outbreak of C. difficile infection (CDI) associated with fluoroquinolone-resistant North American pulsed-field gel electrophoresis type 1 (NAP1) strains [7]. …”
Section: Introductionmentioning
confidence: 99%